(untitled) (Raparin Journal of Humanities (RJH), 2025)
Rhythm is one of the important elements in poetry, because the poetic form shaped on it. The stronger rhythm is, the stronger poetry is. Therefore, since the old days, poets have felt the importance of rhythm and used many techniques to find a strong rhythm, and repetition is surely one of the main and such as most important techniques. at the sound, word, sentence and meaning level. Word repetition is an important technique, and was used in all stages of poetry, such as, popular poetry, classical poetry, new poetry, and modern poetry. In all of stages, repetition was an essential rhythmic element, especially in popular (folklore) poetry, stage and that’s because of simple song, because the composer of the poetry was a simple persons, that is why they resort to simple ways. word repetition was used in all Kurdish folk songs, whether they were metrical or not, but there is no doubt that the poets in metrical songs relied on it more than in unmetrical songs. This is in order to serve the external rhythm. And to give a special interest and strong rhythm to this sort of song whoever reads Kurdish folk songs will feel beginning repetition, in most songs. This repetition assists to find essential. Metrical that the composer wants meanwhile by controlling bring and talce repeated words has arranged the rhythm of the song.